2018
DOI: 10.3390/nano8070553
|View full text |Cite
|
Sign up to set email alerts
|

Facile Strategy for Synthesizing Non-Stoichiometric Monoclinic Structured Tungsten Trioxide (WO3−x) with Plasma Resonance Absorption and Enhanced Photocatalytic Activity

Abstract: Oxygen vacancy defects play an important role in improving the light-capturing and photocatalytic activity of tungsten trioxide (WO3). However, the hydrogen treatment method that is commonly used to introduce oxygen vacancies is expensive and dangerous. Therefore, the introduction and control of oxygen vacancy defects in WO3 remains a challenge. Here, we demonstrated that oxygen vacancies could be successfully introduced into WO3−x while using a facile method through low temperature annealing in alcohol. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…[27][28][29] Thes light positive shifts of the binding energy of O1sa nd W4fi nH TA-WO 3 /WO 3Àx compared with WO 3 can be attributed to the increased W 6 + ÀOb ond binding energy and oxygen vacancies to maintain the original crystal structure and stability. [30] Moreover,D al Santo and co-workers also reported positive shifting phenomenai nt he XPS peak of TiO 2Àx because of the presence of oxygen vacancies. [31] The peaks at 487 and 496 eV correspond to the binding energies of Sn 3d 5/2 and Sn 3d 3/2 ,r espectively ( Figure S4 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
“…[27][28][29] Thes light positive shifts of the binding energy of O1sa nd W4fi nH TA-WO 3 /WO 3Àx compared with WO 3 can be attributed to the increased W 6 + ÀOb ond binding energy and oxygen vacancies to maintain the original crystal structure and stability. [30] Moreover,D al Santo and co-workers also reported positive shifting phenomenai nt he XPS peak of TiO 2Àx because of the presence of oxygen vacancies. [31] The peaks at 487 and 496 eV correspond to the binding energies of Sn 3d 5/2 and Sn 3d 3/2 ,r espectively ( Figure S4 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
“…MRS studies of WOy films showed (Figure 1b) that a fairly perfect crystalline structure of WOy films was formed at dry air pressures of 40 and 60 Pa. This was indicated by the peaks characteristic of the WO3 monoclinic phase at 271.8, 722.3, and 806.7 cm −1 [36,37]. In this case, no obvious differences in the MRS spectra of these films were observed.…”
Section: The Structure and Composition Of Wo Y Filmsmentioning
confidence: 86%
“…Although typically labelled simply 'WO 3 ', it is rare for the stoichiometry to be exactly 3 : 1; as-synthesized WO 3 is typically slightly oxygen decient. Promoting and tuning the oxygen vacancy (O vac ) concentration can enhance various properties, notably visible light absorption for photoactivity 100 and adsorption energy of various molecules for catalytic or sensing applications. 101 Incorporating oxygen vacancies or other defects into nanosheet surfaces can further improve their photocatalytic activity.…”
Section: Effect Of Oxygen Vacanciesmentioning
confidence: 99%